SWOT Analysis: Implementation of National Education Standard Policy to Improve the Quality of High School Graduates - Orpa, Eri; Madhakomala, R. (PT FORMOSA CENDEKIA GLOBAL, 2024)
The competence of quality graduates cannot be separated from the relationship between each educational standard that is a reference for management, governance, and education. The purpose of this analysis is to examine the implementation of national education standard policies as guidelines for improving the quality of education governance based on the quality of graduates who are ready to compete in the world of work both nationally and at the global level. The approach used in this analysis is descriptive-qualitative, which involves processing data obtained through literature studies in the form of reference books, scientific journals, official documents, digital sites, and official information that can be accessed online. The results of the study on the topic above conclude that SWOT analysis can be used as an alternative management analysis tool to identify aspects of strengths, challenges, opportunities, and threats to improve the quality and competence of graduates in accordance with the policies of national education standards. The results of the SWOT analysis recommend alternative strategies that can be developed and followed up as a form of implementation for improving the quality of graduates.